PROFITABILITAS, LIKUIDITAS, DAN LEVERAGE OPERASI TERHADAP STRUKTUR MODAL - Marcella Clarissa Seprianti Todje; Fajar Rina Sejati; Siti Mariani Basannang (CV. Denasya Smart Publisher, 2025)
This research aims to examine the influence of profitability, liquidity and operating leverage on capital structure. The population in this research is Construction Sub-Sector Companies listed on the Indonesia Stock Exchange for the 2018-2023 period. The sample of companies that meet the purposive sampling criteria is 16 companies. The research data that can be processed is 96 data. The data analysis technique uses multiple regression analysis. The research results show that profitability and liquidity have a significant negative effect on capital structure. Meanwhile, operating leverage has a significant positive effect on capital structure.